Effectiveness of the Digging through Thrombus Technique by Using an Aspiration Catheter and Stent Retriever for Cerebral Venous Thrombosis - Rio HIGAKI; Shinya YAMAGUCHI; Hironori HARUYAMA; Masato OSAKI; Shuji ARAKAWA; Tetsuro SAYAMA (Neurologia Medico-Chirurgica, 2022)
Cerebral venous thrombosis (CVT) is a rare cause of stroke, and the first-line treatment is systemic anticoagulation. Patients unresponsive to standard therapy for CVT present with rapid neurological deterioration and require endovascular treatment. We encountered two patients with severe CVT who underwent endovascular treatment. In our cases, the thrombus was too hard and extensive to pass through using currently existing techniques. We performed the “digging through thrombus technique” using an aspiration catheter and stent retriever and achieved rapid sinus recanalization and favorable outcomes.